The Effect of Workload, Job Conflict, and Work Stress on Job Satisfaction - Ghifari, Hafiyyan; Dodi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the effects of workload, work-family conflict, and work-related stress on employee job satisfaction at PT Askrindo. Design/Methodology/Approach – This study employs a quantitative research approach. The population consists of 71 employees from the Compliance Division, Human Resource Division, and Risk Management Division of PT Askrindo. Using a saturated sampling technique, all members of the population were selected as respondents. Primary data were collected through Likert-scale questionnaires and analyzed using multiple linear regression to examine the effects of workload, work-family conflict, and work-related stress on job satisfaction. Findings – The results indicate that workload and work-related stress have significant partial effects on employee job satisfaction. Meanwhile, work-family conflict does not have a significant effect on employee job satisfaction. These findings suggest that organizations need to carefully manage employee workload and work-related stress to improve job satisfaction and support better human resource outcomes. Originality/Value This research is original in simultaneously examining workload, work-family conflict, and work-related stress in a single analytical model. The findings provide practical value by helping management prioritize human resource interventions that most effectively improve employee well-being.